RETRACTED : The Effect of Financial Compensation, Intrinsic Motivation and Physical Work Environment on the Performance of Employees of the Human Resources Development Agency of the Ministry of Home Affairs of the Republic of Indonesia - Intan Ayu Nur Khasanah; Ahmad Cik; Kumba Digdowiseiso (Journal of Social Science)
This study aims to determine the effect of financial compensation, intrinsic motivation and physical work environment on the performance of employees of the Human Resources Development Agency of the Republic of Indonesia. The type of research used is quantitative research. This study used primary data by distributing questionnaires as many as 138 respondents. Data analysis uses descriptive and inferential analysis. In the implementation of the study using primary data obtained through the distribution of questionnaires and processed with SPSS 25. The results of the study showed that the financial compensation variable (X1) had a positive and significant effect on the performance of employees of the Human Resources Development Agency of the Republic of Indonesia. The intrinsic motivation variable (X2) has a positive and significant effect on the performance of employees of the Human Resources Development Agency of the Republic of Indonesia. Physical work environment variables (X3) have a positive and significant effect on the performance of employees of the Human Resources Development Agency of the Republic of Indonesia.